(untitled) (Baltic Journal of Sport and Health Sciences, 2022)
Background: Nowadays, infographics have become a very popular visual communication format in diverse sectors, including sports. Their use ranges from very formal sports data presentations (e.g., the introduction of the results from worldwide studies) to less formal occasions (e.g., promotion of any physical activity on social media sites). While the graphical design of sports infographics might be greatly facilitated by modern infographic tools, the formulation of captivating textual information, especially in titles and subtitles, remains a complicated task for their designers. Therefore, the study aims to analyze the most common tactics and practices applied when formulating titles and subtitles in sports infographics. Methods: 50 sports infographics targeting the areas of fitness, running and training were chosen for the current study. The content of their titles and subtitles was analyzed using MAXQDA Analytics Pro 2020 software. Results. The results revealed that the most frequent words used in titles and subtitles of sports infographics were training, performance, results, running, endurance, fitness and strength. While the average length of titles was 8 words, the subtitles were made of 2 words on average. Most commonly, the main titles of sports infographics displayed a combination of tactics and were made of two parts separated by a colon. The subtitles were usually formulated with the use of lists, examples, facts, explanations, opinions, teasers or the technique of 5Ws. Conclusion. The results of this study might facilitate the creation of infographics in the sports sector and thus help to increase awareness of sports-related topics among the general audience. Keywords: infographics, design of infographics, sports infographics, titles of sports infographics, subtitles of sports infographics.